Inside Back Cover: Engineering Donor–Acceptor Heterostructure Metal–Organic Framework Crystals for Photonic Logic Computation (Angew. Chem. Int. Ed. 39/2019). Issue 39 (1st August 2019) - Liu, Xiao‐Ting; Wang, Kang; Chang, Ze; Zhang, Ying‐Hui; Xu, Jialiang; Zhao, Yong Sheng; Bu, Xian‐He
Abstract : A rich library of donor–acceptor heterostructure crystals was prepared by a new strategy. In their Research Article onpage 13890 ff., Z. Chang, X.‐H. Bu, et al. show that the directed assembly of crystalline acceptor hosts can facilitate the targeted encapsulation of donor guest molecules. Heterocrystals based on pre‐designed, guest‐dependent donor–acceptor systems can thus be obtained. They allow the modification of the domain emission, crystal morphology, and energy transfer between domains for applications in optical logic computation.